The Influence of Competitive Level on Stretch-Shortening Cycle Function in Young Female Gymnasts - Sylvia Moeskops; Jason S. Pedley; Jon L. Oliver; Rhodri S. Lloyd (MDPI AG, 2022)
This cross-sectional study investigated how stretch-shortening cycle (SSC) function and kinetic variables differed between young female gymnasts of varying competitive levels. Drop jump (DJ) force-time profiles were examined in 118 female gymnasts, sub-divided by competitive level (n = 21 recreational, n = 41 regional and n = 50 elite). DJ force-time data were analyzed to calculate performance and kinetic variables. Participants' SSC function was categorized as poor, moderate, or good, depending on the presence of an impact peak and spring-like behavior. A high proportion of gymnasts across each group were categorized as having "good" or "moderate" SSC function (i.e., >94.8%), with a trend of increasingly better SSC function observed with competitive level. Significant differences in reactive strength index, contact time, time of landing peak force, relative propulsive peak force, impulse, and ratio of braking: propulsive impulse were found between the elite and recreational group (p < 0.05). While SSC function was generally good to moderate, elite gymnasts had a more desirable kinetic jump-landing strategy than recreational level gymnasts. Drop jump kinetic variables appear to distinguish between elite and recreational gymnasts but not between regional standard gymnasts. Practitioners should consider the kinetic profile of gymnasts when benchmarking and setting training objectives.